2016
DOI: 10.1017/jfm.2016.747
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of installed jet noise

Abstract: A semi-analytical model for installed jet noise is proposed in this paper. We argue and conclude that there exist two distinct sound source mechanisms for installed jet noise and the model is therefore composed of two parts to account for these different sound source mechanisms. Lighthill's acoustic analogy and a fourth-order space-time correlation model for Lighthill stress tensor are used to model the sound induced by the equivalent turbulent quadrupole sources, while the trailing-edge scattering of near-fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(40 citation statements)
references
References 51 publications
(80 reference statements)
1
34
0
Order By: Relevance
“…They attributed this amplification to the scattering of the hydrodynamics pressure field near the solid surface edge. Lyu et al confirmed this theory and developed a reliable prediction model [6] based on the hydrodynamic wave scattering. This model demonstrated that the far-field sound amplification can be accurately predicted by incorporating the scattering of near-field hydrodynamic evanescent waves using Amiet's approach [7].…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…They attributed this amplification to the scattering of the hydrodynamics pressure field near the solid surface edge. Lyu et al confirmed this theory and developed a reliable prediction model [6] based on the hydrodynamic wave scattering. This model demonstrated that the far-field sound amplification can be accurately predicted by incorporating the scattering of near-field hydrodynamic evanescent waves using Amiet's approach [7].…”
Section: Introductionmentioning
confidence: 88%
“…Because near-field pressure azimuthal modes can be used to model scattering noise [6], they are compared using the LES data of isolated and installed jets at the axial location of the plate TE (x∕D 4). The azimuthal decomposition of the near-field pressure spectra is calculated asp…”
Section: Near-field Spectramentioning
confidence: 99%
“…When the surface is placed in the jet acoustic field, where hydrodynamic convective terms can be neglected, the diffraction of acoustic waves from quadrupole sources is predominant; consequently, no significant change of the overall far-field noise intensity relative to the isolated case is found (Cavalieri et al 2014). Instead, if the surface is located in the irrotational region of the jet hydrodynamic field, a strong sound amplification is caused by the scattering of convecting pressure waves at the trailing edge of the solid surface (Cavalieri et al 2014;Lyu, Dowling & Naqavi 2017). Ffowcs-Williams & Hall (1970) showed that this is caused by a change of impedance seen by those hydrodynamic pressure waves at the geometric discontinuity (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In analytical formulations, JIN is usually modeled with the characteristics of a single-stream jet flow and a nearby flat plate, representing the airframe surface. These models can capture very well the effects of trailing-edge scattering of jet hydrodynamic waves, since they use an exact tailored Green's function to solve the problem of scattering by a half plane [6][7][8]. While these models provide fast-running predictions, there is often a trade-off in terms of geometric simplification.…”
Section: Introductionmentioning
confidence: 99%